Benefits and risks of gene drives for invasive plant management - the case for common tansy - Croghan, Lori; Smith, Alan G.; Tancos, Matthew A.; Anderson, Neil O.; Becker, Roger L. (Frontiers in Agronomy, 2023)
Invasive plants cause significant environmental and economic damage, but land managers have few control options. Common tansy (Tanacetum vulgare) is prevalent in many US states and is one of the most reported invasive plants in Minnesota. Controlling common tansy poses a challenge due to its extensive distribution and association with diverse plant communities. A gene drive is being explored as a genetic biocontrol method for the management of several non-native invasives, including common tansy in North America. Gene drives have emerged as a novel biotechnology application with potential to improve public health, promote conservation, and increase agricultural productivity. In common tansy, gene drives could be developed to target genes that would reduce or eliminate female fertility and consequently inhibit common tansy seed production. Using common tansy as an example, we outline risks associated with the use of gene drive technology for invasive plant control and explain how risks may be mitigated. Understanding potential benefits and risks associated with gene drives in the early stages of development is crucial. Mitigating risks, receiving stakeholder input, and navigating the regulatory environment will play an important role in gene drive development and deployment.